2003
DOI: 10.1161/01.atv.0000085842.20866.6a
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Attenuates Development of Angiotensin II–Induced Aortic Abdominal Aneurysm in Apolipoprotein E–Deficient Mice

Abstract: Objectives-Angiotensin II (Ang II) promotes vascular inflammation, accelerates atherosclerosis, and induces abdominal aortic aneurysm (AAA). These changes were associated with activation of nuclear factor (NF)-B-mediated induction of proinflammatory genes. The incidence of AAA in this model was higher in male than in female mice, and the vascular effects of estrogen may be associated with anti-inflammatory actions. The present study was undertaken to test the hypothesis that estrogen can attenuate Ang II-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 56 publications
4
58
0
Order By: Relevance
“…82 Studies on AAA animal models showed that female sex hormones regulate certain cytokines, chemokines, and other proteins with the majority consisting of members of MAPKs, such as AKT, JNK, ERK, and as a result, they inhibit the expression and activity of certain MMPs, especially MMP2 and MMP9, providing a protective role in aneurysm formation. Moreover, the anti-inflammatory effects of estradiol are mediated through downregulation of several nuclear factor kB (NFkB)edependent proinflammatory mediators such as intracellular adhesion molecule 1, vascular cellular adhesion molecule 1, selectin E, monocyte chemotactic protein 1 (Mcp-1), and macrophage colony-stimulating factor in the aorta, 71 while there is evidence of reciprocal antagonism between estrogen receptors and NF-kB activity. 83 As a result, macrophage and leukocyte infiltration is decreased in the aortic wall and the subsequent production of MMPs, preventing the degradation of ECM in the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Studies on AAA animal models showed that female sex hormones regulate certain cytokines, chemokines, and other proteins with the majority consisting of members of MAPKs, such as AKT, JNK, ERK, and as a result, they inhibit the expression and activity of certain MMPs, especially MMP2 and MMP9, providing a protective role in aneurysm formation. Moreover, the anti-inflammatory effects of estradiol are mediated through downregulation of several nuclear factor kB (NFkB)edependent proinflammatory mediators such as intracellular adhesion molecule 1, vascular cellular adhesion molecule 1, selectin E, monocyte chemotactic protein 1 (Mcp-1), and macrophage colony-stimulating factor in the aorta, 71 while there is evidence of reciprocal antagonism between estrogen receptors and NF-kB activity. 83 As a result, macrophage and leukocyte infiltration is decreased in the aortic wall and the subsequent production of MMPs, preventing the degradation of ECM in the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…64 The protective effects of estrogens were confirmed by other studies. 69,70 Additionally, Martin-McNultry et al 71 demonstrated that infusion of AngII induced AAA in 90% of Apoe À/À mice, whereas with 17b-estradiol treatment, only 42% of mice developed AAAs. In another AAA study, tamoxifen, a selective estrogen receptor modulator, decreased neutrophil infiltration and increased catalase expression.…”
Section: Exogenous Estrogens In Aaamentioning
confidence: 99%
“…Both monocyte adhesion and VCAM1 expression were aggravated by oophorectomy and these were reversed after treatment of female animals with E 2 . Later studies performed on hypercholesterolemic Apoe-deficient animals confirmed the pivotal role of endothelial VCAM1 expression for the atheroprotective effects of estrogens (Gourdy et al 2003, Martin-McNulty et al 2003.…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 91%
“…Available results indicate, however, that estrogens reduce atherosclerotic burden in orchidectomized Apoe KO mice on cholesterol-rich diet or infused with angiotensin II (Ang-II) as well as in diabetic Apoe KO mice (Elhage et al 1997a, Tse et al 1999, Martin-McNulty et al 2003. It ought to be emphasized that plasma E 2 concentrations in treated male animals were comparable to those encountered in normal female animals.…”
Section: Effects Of Estrogens On Atherosclerosis In Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation